Development and Evaluation of a Blood Glucose Monitoring YouTube Video for Marshallese Patients Using a Community-Based Participatory Research Approach. (November 2019) - McElfish, Pearl A.; Rowland, Brett; Riklon, Sheldon; Aitaoto, Nia; Sinclair, Ka'imi A.; Ima, Shumona; Kadlubar, Susan A.; Goulden, Peter A.; Hudson, Jonell S.; Mamis, Sammie; Long, Christopher R.
The purpose of this study was to (a) describe the development of a culturally appropriate glucose monitoring video using a community-based participatory research approach and (b) assess the cultural appropriateness and effectiveness of the video. The topic of the video—using a glucometer and the importance of performing blood glucose checks—was chosen by Marshallese community stakeholders. The video was produced in Marshallese with English subtitles and disseminated through YouTube. Participants were recruited from August 16, 2016 to September 12, 2016 in a diabetes clinic that serves Marshallese patients in northwest Arkansas. Fifty participants completed a survey at pre- and postintervention, with questions capturing demographic information and questions on glucose monitoring self-efficacy using an adapted version of the Stanford Patient Education Research Center's Diabetes Self-Efficacy Scale. Twenty of those participants who completed the survey also completed semistructured interviews that assessed cultural appropriateness and effectiveness of the video. Participants reported significant increases in self-efficacy related to glucometer use and the importance of performing blood glucose checks ( p < .001) and a 1.45% reduction in A1C between preintervention and 12 weeks postintervention ( p = .006). Qualitative results indicated the video was both culturally appropriate and effective. The findings of this study were consistent with evidence in the literature, which shows health education videos can be effective at improving health behaviors. Using a community-based participatory research approach to prioritize video topics, and including members of the community in the creation and dissemination of the videos, could aid in ensuring the videos are effective and culturally appropriate.